2016
DOI: 10.5897/ajpp2015.4417
|View full text |Cite
|
Sign up to set email alerts
|

Bioinorganic elemental content of the Ghanaian aphrodisiac medicinal plant, Paullina pinnata Linn. (Sapindaceae)

Abstract: Macro and micro element content of dried roots sample of Paullinia pinnata Linn. (Sapindaceae) in Ghana were analyzed using energy-dispersive x-ray fluorescence (ED-XRF) technique. The aim was to study the possible quantitative correlation between the measured elements and the traditional usage of the plant in the treatment of sexual dysfunction or enhancing/sustaining penile erection. The analyses yielded forty-five (45) elements, of which the concentrations of four (4) elements-calcium, magnesium, potassium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Patients with ED are more prone to DM, hypertension, premature ejaculation, benign prostatic hypertrophy, and overactive bladder compared with the general male population [18,19]. Patients with ED oftentimes suffer from anxiety when sexual ability declines, mutual mistrust, general unhappiness, and fear of losing support from their partner rises [20]. A study reported a greater prevalence of dementia amongst men with long-standing ED (2.5%) compared to controls (1.5%) and that men with ED are 1.68-times more likely to develop dementia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ED are more prone to DM, hypertension, premature ejaculation, benign prostatic hypertrophy, and overactive bladder compared with the general male population [18,19]. Patients with ED oftentimes suffer from anxiety when sexual ability declines, mutual mistrust, general unhappiness, and fear of losing support from their partner rises [20]. A study reported a greater prevalence of dementia amongst men with long-standing ED (2.5%) compared to controls (1.5%) and that men with ED are 1.68-times more likely to develop dementia [7].…”
Section: Introductionmentioning
confidence: 99%
“…A high concentration of magnesium could enhance the production of androgen, estrogens, hormones and neurotransmitters through numerous mechanisms to trigger sexual desire in males. (41,42,45). Sodium and potassium helped in the maintenance of human body tissues excitability, ionic balance, gastric juice formation in the stomach and contraction of muscles.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…It was reported that T. capensis contains Ca, K, Mg, Na, Fe and Zn which are essential nutrients and have reportedly been used for the treatment of infertility and sexual performance enhancement (39). Calcium has been reported to play an important role in bones and teeth formation, proper heart and muscles functioning, penile erection and sustenance or triggering sexual desire in males (40)(41)(42)(43).…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For each plant part, the pellets were prepared in triplicates. The ED XRF was then used to determine the elements present in the plant samples via the radiations emitted from the X-ray tube (44).…”
Section: Elemental Analysismentioning
confidence: 99%